El "fast-food" y el apresuramiento alimentario en México - David Oseguera Parra (Estudios sobre las Culturas Contemporáneas)
A discussion on the "fast-food" like a new canon of food in the world and Mexico from a sociocultural perspective. Fast-food runs at the same time that a universal pressure of meals (considered as social institutions). The roots of both phenomena are reorganizations processes of households and culinary strategies to gain efficiency. In spite of revolution in the family food over recently decades, the coiKlusion is that traditional cooking was not replaced by the industry (source of food fast and cheap, as it is supposed).